2008 WAR IN GEORGIA AND USA POSITION - Lali Kapanadze; Joseph Boccuzzi (International Journal of Innovative Technologies in Social Science, 2023)
This article traces the historical evolution of the diplomatic relations between the United States and Georgia, focusing on key events from the recognition of Georgia’s independence in 1991 to the present day. The narrative explores the dynamics of the Russo-Georgian relationship and the pivotal role the United States played in supporting Georgia’s democratic aspirations, particularly in its pursuit of NATO membership. The analysis delves into critical moments such as the 2008 war between Russia and Georgia, shedding light on the U.S. stance and its impact on subsequent international developments, including Russia’s invasion of Ukraine in 2014. The article highlights the continuity of U.S. support for Georgia across various administrations, emphasizing the consistent theme of backing Georgia’s territorial integrity, sovereignty, and democratic principles. Special attention is given to the strategic partnership between the two nations, as reflected in the 2009 Strategic Partnership Charter and subsequent reaffirmations. The study concludes by discussing the current geopolitical landscape, where President Joseph Biden’s firm stance against Russian aggression aligns with historical U.S. commitments to Georgia. The article underscores the enduring significance of the U.S.-Georgia relationship and its broader implications for regional stability and democratic values.